Actionable Tumor Alterations and Treatment Protocol Enrollment of Pediatric and Young Adult Patients With Refractory Cancers in the National Cancer Institute–Children's Oncology Group Pediatric MATCH Trial. Issue 20 (10th July 2022) - Parsons, D. Williams; Janeway, Katherine A.; Patton, David R.; Winter, Cynthia L.; Coffey, Brent; Williams, P. Mickey; Roy-Chowdhuri, Sinchita; Tsongalis, Gregory J.; Routbort, Mark; Ramirez, Nilsa C.; Saguilig, Lauren; Piao, Jin; et al.
Abstract : PURPOSE: The National Cancer Institute–Children's Oncology Group Pediatric MATCH trial aimed to facilitate evaluation of molecular-targeted therapies in biomarker-selected cohorts of childhood and young adult patients with cancer by screening tumors for actionable alterations. PATIENTS AND METHODS: Tumors from patients age 1-21 years with refractory solid tumors, lymphomas, or histiocytic disorders were subjected to cancer gene panel sequencing and limited immunohistochemistry to identify actionable alterations for assignment to phase II treatment arms. The rates of treatment arm assignment and enrollment were compared between clinical and demographic groups. RESULTS: Testing was completed for 94.7% of tumors submitted. Actionable alterations were detected in 31.5% of the first 1, 000 tumors screened, with treatment arm assignment and enrollment occurring in 28.4% and 13.1% of patients, respectively. Assignment rates varied by tumor histology and were higher for patients with CNS tumors or enrolled at Pediatric Early Phase Clinical Trials Network sites. A reported history of prior clinical molecular testing was associated with higher assignment and enrollment rates. Actionable alterations in the mitogen-activated protein kinase signaling pathway were most frequent (11.2%). The most common reasons provided for not enrolling on treatment arms were patients receiving other treatment or poor clinical status. CONCLUSION: The Pediatric MATCH trial has proven the feasibility of a nationwide screening Protocol for identification of actionable genetic alterations and assignment of pediatric and young adult patients with refractory cancers to trials of molecularly targeted therapies. These data support the early use of tumor molecular screening for childhood patients with cancer whose tumors have not responded to standard treatments. Abstract :